Electroacupuncture Restores Locomotor Functions After Mouse Spinal Cord Injury in Correlation With Reduction of PTEN and p53 Expression - Wei, Zhe; Zhao, Weijiang; Schachner, Melitta (Frontiers in Molecular Neuroscience, 2018)
Background: Our previous studies showed that electro-acupuncture (EA) at Jiaji points promotes expression of adhesion molecule L1 in spinal cord tissue after spinal cord injury (SCI) and contributes to recovery of neural functions. Objective: We investigated the effects of EA on downstream signaling molecules of L1 and molecules relevant to apoptosis with the aim to understand the underlying therapeutic mechanisms. Methods: Female C57BL/6 mice were divided into a sham group, injury group, injury+acupuncture (AP) group and injury+EA group. We investigated the changes of L1-triggered signaling molecules after SCI by immunofluorescence staining and immunoblot analysis. Results: The protein levels of phosphatase and tensin homolog (PTEN) and p53 were decreased by EA at different time points after injury. On the other hand, the levels of phosphorylated mammalian target of rapamycin (mTOR), Akt and Erk were increased. In addition, the level of myelin basic protein (MBP) was increased by EA. AP alone showed less pronounced changes in expression of the investigated molecules. Conclusions: We propose that EA contributes to neuroprotection by inhibiting PTEN and p53 expression and by increasing the levels of phosphorylated mTOR/Akt/Erk and of MBP after SCI. These observations allow novel insights into the beneficial effects of EA via L1-triggered signaling molecules after SCI.